3b - it is a known theorem
4a
"x=\\frac{\\begin{vmatrix}\n 1 & 2 & 3 \\\\\n 4 & 2 & 1\\\\\n 0&3&2\n\\end{vmatrix}}{\\begin{vmatrix}\n 1 & 2 & 3 \\\\\n 3 & 2 & 1\\\\\n1&3&2\n\\end{vmatrix}}=\\frac{4+36-16-3}{4+2+27-6-12-3}=\\frac{7}{4}"
"y=\\frac{\\begin{vmatrix}\n 1 & 1 & 3 \\\\\n 3 & 4 & 1\\\\\n 1&0&2\n\\end{vmatrix}}{\\begin{vmatrix}\n 1 & 2 & 3 \\\\\n 3 & 2 & 1\\\\\n1&3&2\n\\end{vmatrix}}=\\frac{8+1-12-6}{4+2+27-6-12-3}=-\\frac{3}{4}"
"z=\\frac{\\begin{vmatrix}\n 1 & 2 & 1 \\\\\n 3 & 2 & 4\\\\\n 1&3&0\n\\end{vmatrix}}{\\begin{vmatrix}\n 1 & 2 & 3 \\\\\n 3 & 2 & 1\\\\\n1&3&2\n\\end{vmatrix}}=\\frac{8+9-2-12}{4+2+27-6-12-3}=\\frac{1}{4}"
Comments
Leave a comment